ANALYSIS OF INFLUENCE TQM ON THE PERFORMANCE OF THE SERVICE ORGANIZATION ON PUSKESMAS WORI - Lenehang, Vega R.; Worang, Frederik G.; Arie, Fitty V. (Jurnal EMBA: Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2019)
Abstract: Puskesmas is a concept used in providing health services to the society. It is grounded by one of the basic human needs, that is health. This study aims to determine the influence of Total Quality Management which consists of Teamwork, Education and Training, Continuous Improvement, Obsession with Quality, Customer Focus, on Organizational Performance in Puskesmas Wori Kabupaten Minahasa Utara. Total Quality Management (TQM) is tools to improve performance of organization continuously at each level of operation or process, while Organizational Performance is the critical factors for the effectiveness of the organization itself. This research uses quantitative methods and the total sample is 50 respondents. The result is Teamwork, Education & Training, Customer Focus and obsession with Quality don?t have significant influence on organizational performance do not while simultaneously all Total Quality Management variables have significant influence on Organizational Performance, where Continuous Improvement have significant influence on Organizational Performance. The recommendation is for Puskesmas Wori Kabupaten Minahasa Utara to continuously maintain the performance in all aspect. Keywords: total quality management, teamwork, education and training, continuous improvement, obsession with quality, customer focus, organizational performance.